The Influence of Weight Locus of Control on Physical Appearance Comparison Among Working Women: A Study of Demographic and Behavioral Factors. - Nisa, Fakhr Un; Faiz, Aasia; Kashif, Muhammad; Ali Khan Jafri, Mahmood; Ali Shah, Syed Mahboob (Journal of Neonatal Surgery, 2025)
Background: the association of weight locus of control and physical appearance comparison in relation to working women. It seeks to determine how body image concerns are affected by either internal or external control over weight, especially in the work place. The findings give an insight into facilitating healthier self-perceptions and weight management practices among employed women. Objectives: To investigate the correlation between weight locus of control and physical appearance comparison among working women. Study Design: A descriptive cross-sectional study Place and Durtion of Study. Department of Psychiatry Rawalpindi Medical University Rawalpindi, Pakistan from jan 2024 to jan 2025 Methods: A descriptive cross-sectional study was carried out among 150 working women in Rawalpindi. The Dieting Belief Scale (DBS) and Physical Appearance Comparison Revised Scale (PACRS) were used to collect the data. Non-probability convenient sampling was used to choose the sample. Pearson correlation, regression analysis, t-tests, and ANOVA were used to analyze data and measure links and demographic differences. Results: The average age among the participants was 34.6 years with a standard deviation of 4.5 years. Substantial dissimilarity existed (p < 0.05) between women who practiced and those who did not practice exercises. Females of the fitness-oriented group were also reported to have lower physical appearance comparison scores (p = 0.02) which implies that there was a correlation between internal control over weight and low comparison scores among women. Conclusion: the adverse correlation of internal weight locus of control and physical appearance comparison. Frequent exercise and body image perfection through fitness objectives may help working women to achieve self-control and enhance body image satisfaction, leading to healthier self-perceptions and behaviors..